Increasing Consumers with Satisfaction Application based Digital Marketing Strategies - Jihan Zanubiya; Lista Meria; Muhamad Alfi Duwi Juliansah (Startupreneur Business Digital (SABDA Journal), 2023)
As technology advances, more complex tools are produced that can be used as a medium in the creation of consumer-focused business operations. More and more businesses are switching from traditional marketing to digital marketing, but there are still many businesses that are less effective in implementing digital marketing strategies. the importance of digital marketing in today's digital era and technological developments that affect the way businesses interact with customers. One way of combining these technologies is marketing practices that utilize digital marketing techniques. The purpose of this research is to evaluate and explore how exposure to digital marketing strategy concepts can increase customer satisfaction using an application basis. The research method used in this research is descriptive, by collecting and analyzing data systematically and objectively. Secondary research data obtained from literature studies in the form of theories and empirical findings from previous studies. The results show that an effective digital marketing strategy includes: a solid understanding of the target market and segmentation, choosing the right marketing platform, interesting and relevant content, search engine optimization, ongoing customer interaction and interest. The conclusion that can be drawn from the findings of the discussion is that an application-based digital marketing strategy, organizations involve an analysis of internal and external elements to choose the best digital marketing approach.